2016
DOI: 10.1681/asn.2014050520
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 29b, 133b, and 211 Regulate Vascular Smooth Muscle Calcification Mediated by High Phosphorus

Abstract: Vascular calcification is a frequent cause of morbidity and mortality in patients with CKD and the general population. The common association between vascular calcification and osteoporosis suggests a link between bone and vascular disorders. Because microRNAs (miRs) are involved in the transdifferentiation of vascular smooth muscle cells into osteoblast-like cells, we investigated whether miRs implicated in osteoblast differentiation and bone formation are involved in vascular calcification. Different levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 44 publications
4
67
1
1
Order By: Relevance
“…In vitro calcification of VSMC has been widely studied using calcification medium, i.e. cell culture medium supplemented with phosphate, calcium and FBS [25,40,47,48]. Using this approach, however, calcification induction was initially variable in our hands.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro calcification of VSMC has been widely studied using calcification medium, i.e. cell culture medium supplemented with phosphate, calcium and FBS [25,40,47,48]. Using this approach, however, calcification induction was initially variable in our hands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that miRNAs play a pivotal role in vascular calcification . We detected eight miRNAs related to calcification in exosomes secreted by VSMCs treated with or without MT by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 94%
“…Some studies have demonstrated that miR‐204 and miR‐211 play a key role in vascular calcification . We hypothesised that exosomal miR‐204 and miR‐211 participated in the process of vascular osteogenic differentiation and senescence by a paracrine mechanism.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Emerging evidence suggests that complex networks of multiple miRs are responsible for the development of vascular calcification, primarily by targeting the osteogenic master regulator RUNX2 (31,32) (Figure 1). Accordingly, miRs might be useful as biomarkers of early vascular calcification, allowing timely intervention to prevent progression of this process (32). In addition, miRs might represent promising targets for the prevention of vascular calcification and its adverse cardiovascular sequelae.…”
Section: Discussionmentioning
confidence: 99%